Facilitators and Barriers of Health Insurance in Eye Morbidity in Makwanpur District, Nepal - Karakheti, Arati; Chaudhary, Roshan Kumar; Karakheti, Ashwin; Kharel, Sagun (Nepal Journal of Health Sciences, 2024)
Introduction: National Health Insurance Program is a financing mechanism of health system that enhance the utilization of health care services and reduce out-of-pocket expenditure in eye health care which can contribute towards universal health coverage. Eye Morbidity is one of the common morbidities in Nepalese population.Objective: Objective of this study is to assess the facilitators and barriers of health insurance program on eye morbidity of Nepal.Methods: This was a qualitative study in which Focus Group Discussion, Face-to-face Interview, Key Informant Interview was conducted to collect qualitative data. Well written informed consent was obtained before data collection. Analysis was done using Dedoose software. Intercoder reliability was checked by research team members to come to an agreement. Socio-ecological model was adopted to access the facilitators and barriers.Results: Long term membership duration, minimal fee of enrollment and renewal, dedicated enrollment assistant and government support as facilitator of eye Health Insurance. Similarly, improper behavior at eye healthcare delivery center, time consuming procedure, inadequate knowledge and awareness, high cost of insurance ticket, inadequate quality and quantity of medicine, negative peer influence, unfriendly health care professional behaviors, difficult and lengthy referral system as major barriers in health insurance program covering eye health and morbidity.Conclusion: Special priority and expansion of coverage to eye health in Health Insurance Program is to be given. and to ensure fundamental rights of citizens.